TRADISI BAJAPUIK MASYARAKAT MINANGKABAU DI PARIAMAN - Andriyansyah; Yulfira Riza (Jurnal Budaya Nusantara, 2022)
In the marriage process, of course, there will be various traditions that are different in each region, for example, such as the bajapuik tradition carried out by the Minangkabau community in Pariaman. This article aims to find out the explanation of the bajapuik tradition, both in terms of its meaning, procedures, and people’s views on the tradition. The method of writing this article is done by using the quantitative causality method, namely library research by reading articles related to the bajapuik tradition. Bajapuik tradition is a pre-wedding activity by giving bajapuik money from the bride’s side to the groom’s side. The amount of the bajapuik money itself depends on the title, education, and occupation of the prospective groom. This tradition has a positive goal, namely to strengthen family relations and to respect each other between the two sides of the bride’s family. Because bajapuik has been carried out for a long time, of course people will get used to it and it will feel strange if there is a wedding in Pariaman that does not use this bajapuik tradition. Those who do not do it will surely get social sanctions in the form of innuendo, gossip and be looked down upon by the local community. The community will assume that the bride’s family does not respect the groom’s family and does not respect the customs that have been implemented so far.